Irrelevant actions, goal demotion and explicit instruction: A study of overimitation. Issue 4 (17th March 2021) - Taniguchi, Yuuki; Sanefuji, Wakako
Abstract: Overimitation is imitating relevant and irrelevant actions to achieve a final goal (Lyons et al., Proceedings of the National Academy of Sciences of the United States of America, 2007, 104(50), 19751–19756). We investigated whether the order of demonstration (the irrelevant action is demonstrated before or after the final goal) induces overimitation when using explicit instruction (saying the instrumental goal). We employed a between‐subjects design with 48 five‐year‐olds. In the before condition, the irrelevant action towards the sub‐apparatus was performed, followed by the action relevant to the final goal with the main apparatus. In the after condition, the experimenter performed the irrelevant action after the final goal. Results indicated that overimitation occurred when irrelevant actions were demonstrated after the goal using explicit instruction. This may mean that children's overimitation is affected by goal demotion, which is created through the order of demonstration of the irrelevant actions. This highlights how goal demotion affects children's overimitation and clarifies how children perceive intentionality in the action sequence, including irrelevant actions.